Band gap control of phononic beam with negative capacitance piezoelectric shunt - 陈圣兵 温激鸿 郁殿龙 王刚 温熙森 (Chinese physics B, 2011)
Periodic arrays of negative capacitance shunted piezoelectric patches are employed to control the band gaps of phononic beams. The location and the extent of induced band gap depend on the mismatch in impedance generated by each patch. The total impedance mismatch is determined by the added mass and stiffness of each patch as well as the shunting electrical impedance. Therefore, the band gap of the shunted phononic beam can be actively tuned by appropriately selecting the value of negative capacitance. The control of the band gap of phononic beam with negative capacitive shunt is demonstrated numerically by employing transfer matrix method. The result reveals that using negative capacitive shunt to tune the band gap is effective.